LENGTH-FREQUENCY DISTRIBUTION IN CYNOGLOSSUS SEMIFASCIATUS DAY ON THE WEST COAST DURING 1980-81 - Seshappa, G; Chakrapani, B K (Indian Journal of Fisheries, 2011)
In general, the seasonal length-frequency trends of Cynoglossus semifasciatiisshowed a rough agreement with the past findings at Calicut, but with some differences.The pooled data of all the centres together showed the main mode at 10.5-10.9 cm in May and 11.5-11.9 cm in October, the length range in the latter monthbeing 8.4-16.4 cm, two smaller modes of May were represented by a single mode at13-13.4 cm in October there being, however, other minor modes in both the months.New juveniles were seen in the catches in November and December, the motlalgroups in the latter month being at 8-8.4 cm and 12-12.4 cm. The dominant highersize modes of four of the premonsoon months and also of October in the pooleddata of 1980 were rather low as compared to the generalised trend of the earlieryears of published work at Calicut. The cause for this apparent decline in the sizeof the mode is perhaps due to the large scale trawling during the past decade.The total length ranged from 6.35 cm to 16.4 cm taking all the samples together,the sample mean lengths ranging from 8.43 cm to 13.96 cm. The Standard Deviation(SD), Standard Error (SE) and the coefficient of Variation (CV) havealso been worked out and tabulated.The total lengths of two samples from Cochin taken during January 1982are also considered separately, in the tables.